The crisis status of Ukrainian society as a result of the “people-authority” dialogue’s lack - Довбня, О. М.; Довбня, О. М. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
The article is considered the problems of Ukrainian society’s splitting during Ukraine’s Independence, and the impossibility of negotiation process between authorities and majority of population is also regarded. The impact of civic society’s immaturity and sense of the civic responsibility to the tragic events in 2013-2014 years in Ukraine are investigated. Also the role of the country’s oligarchic clans in the formation of negative forms of political participation of some regions is considered.